Nursing practice in the prevention and screening of cervical cancer: An integrative literatura review (Research, Society and Development, 2025)
The prevention and early diagnosis of cervical cancer remain ongoing challenges for health systems and represent a priority field of nursing practice in Primary Health Care. This study aimed to identify, through an integrative literature review, the available evidence regarding nursing practices in the prevention and screening of cervical cancer within the Brazilian Unified Health System (SUS). The search was carried out in the SciELO, LILACS, BDENF, and PubMed databases using the descriptors “nursing,” “prevention,” “cervical cancer,” and “primary health care.” A total of 25 studies published between 2015 and 2025 were included. The analysis led to the identification of three thematic axes: health education and prevention, screening and early diagnosis, and challenges in nursing practice. The findings indicate that nurses play a key role in health education, cytopathological examination performance, follow-up of results, and coordination with other levels of care. However, structural and sociocultural barriers still hinder women’s adherence to preventive actions and the achievement of screening targets. It is concluded that professional qualification, continuing education, and the strengthening of public health policies are essential to consolidate nursing as a leading force in the prevention of cervical cancer.